Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) Dalam Penentuan Lokasi Pemasaran Produk - Dwi Handoko (CV. Keranjang Teknologi Media, 2024)
Product marketing location determination is a strategic decision that requires in-depth analysis to maximize market reach and distribution efficiency. One of the main problems is the high level of competition in an area, which can reduce the attractiveness of a business and limit growth. In addition, a mistake in understanding the dominant customer profile in a particular location can result in a mismatch between the product offering and market needs. This study aims to determine the location of product marketing by utilizing a decision support system technology and applying the MOORA method as an approach in recommending a decision. The ranking results of the MOORA method recommend Location 1 as a product marketing location with a final value of 0.5379 by getting a rank of 1, Location 3 as a product marketing location with a final value of 0.4907 by getting a rank 2, and Location 1 as a product marketing location with a final value of 0.4742 by getting a rank 3.